Forever young white dwarfs : when stellar ageing stops - Camisassa, María Eugenia (2021)
White dwarf stars are the most common end point of stellar evolution. The ultramassive white dwarfs are of special interest as they are related to type Ia supernovae explosions, merger events, and fast radio bursts. Ultramassive white dwarfs are expected to harbour oxygen-neon (ONe) cores as a result of single standard stellar evolution. However, a fraction of them could have carbon-oxygen (CO) cores. Recent studies, based on the new observations provided by the Gaia space mission, indicate that a small fraction of the ultramassive white dwarfs experience a strong delay in their cooling, which cannot be solely attributed to the occurrence of crystallisation, thus requiring an unknown energy source able to prolong their life for long periods of time. In this study, we find that the energy released by 22Ne sedimentation in the deep interior of ultramassive white dwarfs with CO cores and high 22Ne content is consistent with the long cooling delay of these stellar remnants. On the basis of a synthesis study of the white dwarf population, based on Monte Carlo techniques, we find that the observations revealed by Gaia can be explained by the existence of these prolonged youth ultramassive white dwarfs. Although such a high 22Ne abundance is not consistent with the standard evolutionary channels, our results provide evidence for the existence of CO-core ultramassive white dwarfs and for the occurrence of 22Ne sedimentation.